The chemokine network. II. On how polymorphisms and alternative splicing increase the number of molecular species and configure intricate patterns of disease susceptibility - Colobran, R (Blackwell Science Inc, 2007)
In this second review on chemokines, we focus on the polymorphisms and alternative splicings and on their consequences in disease. Because chemokines are key mediators in the pathogenesis of inflammatory, autoimmune, vascular and neoplastic disorders, a large number of studies attempting to relate particular polymorphisms of chemokines to given diseases have already been conducted, sometimes with contradictory results. Reviewing the published data, it becomes evident that some chemokine genes that are polymorphic have alleles that are found repeatedly, associated with disease of different aetiologies but sharing some aspects of pathogenesis. Among CXC chemokines, single nucleotide polymorphisms (SNPs) in the CXCL8 and CXCL12 genes stand out, as they have alleles associated with many diseases such as asthma and human immunodeficiency virus (HIV), respectively. Of CC chemokines, the stronger associations occur among alleles from SNPs in CCL2 and CCL5 genes and a number of inflammatory conditions. To understand how chemokines contribute to disease it is also necessary to take into account all the isoforms resulting from differential splicing. The first part of this review deals with polymorphisms and the second with the diversity of molecular species derived from each chemokine gene due to alternative splicing phenomena. The number of molecular species and the level of expression of each of them for every chemokine and for each functionally related group of chemokines reaches a complexity that requires new modelling algorithms akin to those proposed in systems biology approaches.